1985
DOI: 10.1113/jphysiol.1985.sp015746
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal plexus and electrolyte transport across rat colonic mucosa.

Abstract: SUMMARY1. Electrolyte transport across two preparations of mucosa from rat colon descendens was compared to determine what influence the submucosal plexus has on electrolyte transport. One preparation consisted of the mucosa, muscularis mucosae, and the submucosal tissue and is referred to as the mucosa-submucosa preparation. The second preparation obtained by further blunt dissection ofthe mucosa-submucosa preparation consisted of only the mucosa and the circular muscle layer of muscularis mucosae and is refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 24 publications
6
56
2
Order By: Relevance
“…This suggests that PGE2 may regulate hexose absorption and metabolism by influencing submucosal release of neurotransmitters from the enteric neural network. Spontaneously active neurons from the submucosal plexus are thought to have a direct or indirect inhibitory influence on the mucosa (Andres, Bock, Bridges, Rummel & Schreiner, 1985;Ahsan, Naftalin & Smith, 1988). Certainly, we observed that a-MG uptake by isolated epithelial cells in the present study was enhanced by carbachol and noradrenaline.…”
Section: Resultssupporting
confidence: 63%
“…This suggests that PGE2 may regulate hexose absorption and metabolism by influencing submucosal release of neurotransmitters from the enteric neural network. Spontaneously active neurons from the submucosal plexus are thought to have a direct or indirect inhibitory influence on the mucosa (Andres, Bock, Bridges, Rummel & Schreiner, 1985;Ahsan, Naftalin & Smith, 1988). Certainly, we observed that a-MG uptake by isolated epithelial cells in the present study was enhanced by carbachol and noradrenaline.…”
Section: Resultssupporting
confidence: 63%
“…Indeed, TTX had no effect on net Na+ or C1-fluxes in distal colonic tissues of 6-to 10-wk-old weaned pigs (18), although the neurotoxin appears to have variable effects on basal Isc (19). In other intestinal tissues in which a significant effect of TTX on basal Isc has been observed, addition of the neurotoxin increases Na+ and Cl-absorption (20)(21)(22)(23). This suggests that in the basal state, ongoing activity of submucosal neurons limits the absorptive capacity of the epithelium for these ions (20,23).…”
Section: Efs Carb Ne 5-htmentioning
confidence: 99%
“…Recent studies indicate that enteric nerves, especially submucosal nerves, influence electrolyte transport in the colon (Ander, Bock, Bridges, Rummel & Schreiner, 1985;Rangachari & McWade, 1986;Kuwahara, Bowen, Wang, Condon & Cooke, 1987).…”
Section: Introductionmentioning
confidence: 99%